MAKNA PADA PROSES PELAKSANAAN UPACARA ADAT KALOMBA PADA MASYARAKAT DI DESA BONTO BIRAENG KECAMATAN KAJANG KABUPATEN BULUKUMBA - Nurilmi, Nurilmi; M, Hasbi; AT, M Ramli (Jurnal Ilmiah Global Education, 2023)
This study discusses the ritual of the Kalomba Traditional Ceremony as a community belief in Bonto Biraeng Village, Kajang District, Bulukumba Regency. This study uses a qualitative method. Informants were selected using a purposive sampling technique. The collection of data used is observation, interview, and documents. in analyzing a data can be done by means of data reduction, data presentation, and drawing conclusions. The traditional Kalomba tradition is carried out based on stages starting from the maje'ne procession (ablution), burning incense and lighting candles, reading prayers, shaking off the incense smoke, the tompong procession, the baccing child procession, the paddinding-dindinggi stage, the installation of kampalo and the massolo event (giving money to children) and the event ends with a meal together by family and relatives. The meaning of the traditional Kalomba tradition is as medicine and safety to avoid skin diseases and is meaningful as a thanksgiving for parents to children. From the traditional Kalomba tradition, it reveals the value of mutual assistance and togetherness, establishing friendship and responsibility.